Perempuan Berkemajuan dan Poligami: Analisis Pandangan Organisasi Aisyiyah dalam Konteks Gender di Era Kontemporer - Dzakkir, Abdul (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2025)
Women's progress is a concept raised by Aisyiyah in fighting for gender equality, eliminating backwardness and injustice for women. One of the topics discussed by Aisyiyah is polygamy, which is considered gender-biased where women are the losers. The purpose of this study is to describe the concept of progressive women in understanding polygamy in the context of today's society. This type of research is a literature study with a descriptive qualitative approach. The result of the research is that Aisyiyah views that Islam does not introduce the concept of polygamy, rather Islam comes as a rule that corrects the habit of polygamy. In the present context, polygamy can be carried out by considering various aspects, such as social emergencies, not arbitrary, and fulfilling the requirements of justice. In addition, in seeking equality, Aisyiyah offers various concepts such as developing a scientific movement, strengthening the sakinah family, reactualising praxis efforts and empowering women by maximising the role of women in a wider range of sectors.